5(x-7)+14=2(x-6)

Simple and best practice solution for 5(x-7)+14=2(x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-7)+14=2(x-6) equation:


Simplifying
5(x + -7) + 14 = 2(x + -6)

Reorder the terms:
5(-7 + x) + 14 = 2(x + -6)
(-7 * 5 + x * 5) + 14 = 2(x + -6)
(-35 + 5x) + 14 = 2(x + -6)

Reorder the terms:
-35 + 14 + 5x = 2(x + -6)

Combine like terms: -35 + 14 = -21
-21 + 5x = 2(x + -6)

Reorder the terms:
-21 + 5x = 2(-6 + x)
-21 + 5x = (-6 * 2 + x * 2)
-21 + 5x = (-12 + 2x)

Solving
-21 + 5x = -12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-21 + 5x + -2x = -12 + 2x + -2x

Combine like terms: 5x + -2x = 3x
-21 + 3x = -12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-21 + 3x = -12 + 0
-21 + 3x = -12

Add '21' to each side of the equation.
-21 + 21 + 3x = -12 + 21

Combine like terms: -21 + 21 = 0
0 + 3x = -12 + 21
3x = -12 + 21

Combine like terms: -12 + 21 = 9
3x = 9

Divide each side by '3'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x=3x+44 | | 7x^6-2x^5+x^2+5x+2= | | 4y-12=y+12 | | -1+4+7=2x-9 | | (1/3)p=(1/2)p+(1/3) | | -2/5x=-10 | | 0.4y+0.1y=-2.5 | | 27=30-3(6-2c) | | pi/7=a/4 | | x(6x-11)=-5 | | x/-16=-10 | | 23+4=83 | | 3.1415926535897932384626433832795028841971693993751058209749445923078164062862089986280348253421170679821480865132823066470938446095505822317253594081284811174502841027019385211055596446229489549303819644288109756659334461284756482337867831652712019091456 | | 0.8(1.2+5)= | | 4a*2-9b*2+a*2-1+2b*2+5= | | 5x+4=4x-7 | | 3.1415926535897932384626433832795028841971693993751058209749445923078164062862089986280348253421170679821480865132823066470938446095505822317253594081284811174502841027019385211055596446229489549303819644288109756659334461284756482337867831652712019091456 | | 3(x-7)=3x-7(7-x) | | 3r*2r= | | B/13-3b/13=8/23 | | -x^2+6x+34=0 | | -0.3(x-4)+x=1.5+-0.5x | | 6x*4x= | | -6(-17)= | | -397h=16t^2 | | ((5/8)x^2)-8x+72.5=0 | | (5a)2= | | 18x+30= | | 4y+9=-7 | | (5/8)x^2-8x+72.5=0 | | 16=2x+2(x-2) | | v-8=3 |

Equations solver categories